Distinct expression trend of signature antigens of Staphylococcus aureus osteomyelitis correlated with clinical outcomes. Issue 2 (29th December 2020) - Fu, Wei; He, Wenbin; Ren, Youliang; Li, Zhengdao; Liu, Jinyue; Liu, Yi; Xie, Zhao; Xu, Jianzhong; Bi, Qing; Kong, Mingxiang; Lee, Charles C.; Daiss, John L.; et al.
Abstract: The major limitations of clinical outcome predictions of osteomyelitis mediated by Staphylococcus aureus (S. aureus) are not specific and definitive. To this end, current studies aim to investigate host immune responses of trend changes of the iron‐regulated surface determinant (Isd) of IsdA, IsdB, IsdH, cell wall‐modifying proteins of amidase (Amd) and glucosaminidase (Gmd), and secreted virulence factor of chemotaxis inhibitory protein S. aureus (CHIPS) and staphylococcal complement inhibitor (SCIN) longitudinally to discover their correlationship with clinical outcomes. A total of 55 patients with confirmed S. aureus infection of the long bone by clinical and laboratory methods were recruited for the study. Whole blood was collected at 0, 6, 12 months for the serum that was used to test IsdA, IsdB, IsdH, Gmd, Amd, CHIPS, and SCIN using a customized Luminex assay after clinical standard care parameters were collected. The patients were then divided into two groups: (1) infection controlled versus (2) adverse outcome based on clinical criteria for statistical analysis. We found that standard clinical parameters were unable to distinguish therapeutic outcomes. Significant overexpression of all antigens was confirmed in infection patients at 0‐, 6‐, and 12‐month time points. A distinct expression trend and dynamic changes of IsdB, Amd, Gmd, and CHIPS were observed between infection controlled and adverse outcome patients, while the IsdA, IsdH, SCIN remained demonstrated no statistical significance. We conclude that dynamic changes of specific antigens could predict clinical outcomes of S. aureu s osteomyelitis. Clinical Relevance: The trend changes of host immune responses to S. aureus specific antigens of IsdB, Gmd, Amd, and CHIPS could predict clinical outcomes of S. aureu s osteomyelitis.